Investigation of creep behaviour on copper rod at multiple temperature. (2022) - Ojha, Amit; Chauhan, Premanand S.; Sharma, Avadesh K.; Agarwal, Anupma
Abstract: The work is aimed to present the creep behaviour of copper at multiple temperature ranging from 350 °C to 550 °C. The experiments were conducted on the specimen of copper rod of dimensions (ɸ =10.7 mm and length = 420 mm) at multiple temperature providing a constant strain rate. Depending upon the variation in the behaviour of the specimen study has been divided in three different phases primary, secondary and tertiary. In all three phases, increment in elongation and fracture with temperature have been observed which further provides the estimation of Copper deformation rate at 350 °C, 450 °C and 550 °C. As the copper has been widely used to perform various functions at multiple temperatures, this study will help to conceptualize the appropriate uses of copper at higher temperature applications.